Biomimetic Supramolecular Polymer Networks Exhibiting both Toughness and Self‐Recovery. Issue 10 (16th January 2017) - Liu, Ji; Tan, Cindy Soo Yun; Yu, Ziyi; Lan, Yang; Abell, Chris; Scherman, Oren A.
Abstract : Biomimetic supramolecular dual networks : By mimicking the structure/function model of titin, integration of dynamic cucurbit[8]uril mediated host–guest interactions with a trace amount of covalent cross‐linking leads to hierarchical dual networks with intriguing toughness, strength, elasticity, and energy dissipation properties. Dynamic host–guest interactions can be dissociated as sacrificial bonds and their facile reformation results in self‐recovery of the dual network structure as well as its mechanical properties.